2020
DOI: 10.3390/su12177215
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels and Their Potential in South Korea

Abstract: We investigated the biofuel potential of South Korea and the implications of the introduction of biofuels for the Korean fuel market. We approximated the upper-bound biomass potential from forestry residues, livestock manure, and staple crops and calculated the amount of fuel that could be produced using these different biomass feedstocks. Our assessment suggests that biomass can be used to produce a significant portion of the fuel consumed annually in South Korea, with the most promising feedstock being fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another important issue is the rebound effect. For instance, Hochman et al [50] found by their modeling work that the introduction of biofuels increases the amount of total fuel consumed and reduces the average fuel price in South Korea. Therefore, there is an environmentally damaging recovery in which gasoline consumption is reduced by less than the quantity of surplus biofuels.…”
Section: Country-related Analysesmentioning
confidence: 99%
“…Another important issue is the rebound effect. For instance, Hochman et al [50] found by their modeling work that the introduction of biofuels increases the amount of total fuel consumed and reduces the average fuel price in South Korea. Therefore, there is an environmentally damaging recovery in which gasoline consumption is reduced by less than the quantity of surplus biofuels.…”
Section: Country-related Analysesmentioning
confidence: 99%
“…The developed model was then applied to a case study in South Korea, where the current demand for bioethanol is 350 million gallons per year (MGY), to show (a) the optimal mix of feedstocks required for a biorefinery and (b) the optimal supply chain configuration (e.g., the best depot locations, required depot numbers, and sizes). In South Korea, forecasting models have predicted that there will be an annual production of approximately 37 million tons of oil-equivalent renewable energy by 2035, including bioethanol and biodiesel …”
Section: County-level Case Study: South Koreamentioning
confidence: 99%